Figure 10 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 10. Condylostoma spatiosum (A, B), Diophrys scutum (D), Diophrys aff. oligothrix (C, G), Diophrys appendiculata (E), Euplotes vannus (F) and Euplotes dragescoi nov. spec. (H–K) after protargol impregnation. (A) Dorsal view, to show the general appearance, arrow marks the beaded macronucleus. (B) Caudal portion, arrowhead marks the suture. (C) Dorsal view, to show the dorsal kineties (arrows). (D) Ventral view, to show the general infraciliature. (E) Ventral view, arrow marks the pre-transverse cirrus, double-arrowheads indicate the transverse cirri, while arrowhead points to the anterior marginal cirrus. (F) Dorsal view, arrowheads mark the three caudal cirri, arrow indicates the macronucleus. (G) Ventral view, arrow marks the pre-transverse cirrus. (H) Detail of a divider, arrowheads mark the newlyformed two marginal cirri (note the different sizes). (I) Dorsal view, to show the ridges. (J) Ventral view, arrow marks the anterior (large) marginal cirrus, double-arrowheads indicate the paroral membrane. (K) Detail of ventral view, arrow and arrowhead indicate the small and large marginal cirrus, respectively. Scale bars: 200 Mm (A); 100 Mm (D); 50 Mm (E–G, J). Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 1006, DOI:10.1080/00222930701877540, http://zenodo.org/record/5219160